Analisis Self-Regulated Learning dalam Pembelajaran Matematika Pada Siswa SMP - Febriyanti, Fitria; Imami, Adi Ihsan (Universitas Dr. Soetomo, 2021)
Abstract This study aims to analyze how much students have achieved independence in learning. Self-Regulated Learning includes all things student learning independently without the help of others, student learning motivation, or things that affect student independence in learning, especially in learning mathematics. This analytical study will be continued as an effort to increase self-regulated learning. The scope of self-regulated learning is very broad, but it can be analyzed by several methods, one of which is by doing quantitative descriptive with data collection techniques in the form of questionnaires or questionnaires on research objects taken from several populations. In this study, respondents were drawn from a population of students of class VIII D at SMPN 2 Lemahabang Karawang with a total of 25 respondents. The study was conducted with indicators of learning independence as measured by the respondent's ability to respond to the mathematics learning independence scale with 18 statements that can be responded to by respondents with a 5-point Likert scale. After analyzing according to the indicators of learning independence, the data obtained was processed further to determine the percentage of student learning independence phases. From the results of the analysis and evidence of the value of self-regulated learning in material learning, the results for the planning phase (27.47%), the implementation phase (33.02%), and the evaluation phase (24.80%) were obtained. And overall obtained an average of 28.97%. This shows that the application of self-regulated learning in class VIII D students of SMPN 2 Lemahabang Karawang is still very low, so there is a need for efforts to increase self-regulated learning to achieve the desired learning objectives and make students successful in studying. Keywords: Analysis, Likert scale, Self-Regulated Learning Abstrak Tujuan dari penelitian ini yakni menganalisis seberapa besar siswa telah mencapai kemandiriannya dalam belajar. Kemandirian belajar siswa mencakup segala hal belajar siswa secara mandiri tanpa bantuan orang lain, motivasi belajar siswa ataupun hal yang mempengaruhi kemandirian siswa dalam belajar, khususnya dalam pembelajaran matematika. Kajian analisis ini akan dilanjutkan sebagai upaya peningkatan self-regulated learning. Cakupan dari self-regulated learning sangatlah luas, namun dapat dianalisis dengan beberapa metode, salah satunya adalah dengan melakukan deskriptif kuantitatif melalui teknik pengumpulan data berupa angket atau kuisioner pada objek penelitian yang diambil dari populasi. Pada penelitian ini, responden diambil dari populasi siswa kelas VIIID pada SMPN 2 Lemahabang Karawang dengan jumlah 25 responden. Penelitian dilakukan dengan indikator kemandirian belajar yang diukur dari kemampuan responden dalam menyikapi skala kemandirian belajar matematika dengan 18 pernyataan yang dapat ditanggapi oleh responden dengan skala Likert yang memiliki 5 poin. Setelah melakukan analisis sesuai indikator kemandirian belajar, data yang diperoleh diolah secara lanjut untuk mengetahui persentase fase-fase kemandirian belajar siswa. Dari hasil analisis dan pembuktian nilai self-regulated learning pada pembelajaran matematika didapatkan hasil untuk fase perencanaan (27,47%), fase pelaksanaan (33,02%) dan fase evaluasi (24,80%). Dan secara keseluruhan diperoleh rata-rata sebesar 28,97%. Hal tersebut menunjukan bahwa penerapan self-regulated learning pada siswa kelas VIIID SMPN 2 Lemahabang Karawang masih sangat rendah, sehingga perlu adanya upaya dalam meningkatkan self-regulated learning agar tercapai tujuan belajar yang diinginkan serta menjadikan siswa sukses dalam belajarnya. Kata Kunci: Analisis, Self-Regulated Learning, Skala Likert